Macrophage colony-stimulating factor is indispensable for both proliferation and differentiation of osteoclast progenitors. - Tanaka, S (1993)
The mechanism of action of macrophage colony-stimulating factor (M-CSF) in osteoclast development was examined in a co-culture system of mouse osteoblastic cells and spleen cells. In this co-culture, osteoclast-like multinucleated cells (MNCs) were formed within 6 d in response to 10 nM 1 alpha,25(OH)2D3 added only for the final 2 d of culture. Simultaneously adding hydroxyurea for the final 2 d completely inhibited proliferation of cultured cells without affecting 1 alpha,25(OH)2D3-stimulated MNC formation. Autoradiographic examination using [3H]-thymidine revealed that osteoclast progenitors primarily proliferated during the first 4 d, whereas their differentiation into MNCs occurred predominantly during the final 2 d of culture in response to 1 alpha,25(OH)2D3. When anti-M-CSF antibody or anti-M-CSF receptor antibody was added either for the first 4 d or for the final 2 d, the MNC formation was similarly inhibited. In co-cultures of normal spleen cells and osteoblastic cells obtained from op/op mice, which cannot produce functionally active M-CSF, the lack of M-CSF either for the first 4 d or for the final 2 d failed to form MNCs in response to 1 alpha,25(OH)2D3 added for the last 2 d. These results clearly indicate that M-CSF is indispensable for both proliferation of osteoclast progenitors and their differentiation into mature osteoclasts.